The Implementation of Online English Learning Classroom by The English Teachers at SMP Islam Al- Azhar 24 Makassar - Kirana; Andi Tenri Ampa; Junaid (FKIP Unismuh Makassar, 2023)
This study intended to investigate (1) what types of online learning are used by the English teachers at SMP Islam Al- Azhar 24 Makassar (2) How do the English teacher use online Learning at Smp Islam Al-Azhar 24 Makassar.This study use Descriptive Qualitative method. The interwiew question consisted of 20 question, there are 10 question about types of online Learning and 10 how do the english teachers in use online learning. The researcher did the interview at the English teachers who teaches in class of Smp Islam Al-Azhar 24 makassar. The Data analysis was carried out by reducing the data, then presenting the data, and after that drawing conclusions and verification.The result have shown that the types of online learning are used by the English teachers are blendid Learning and hybrid online learning. The teachers mostly use various platform of online learning in teaching English through blended or hybrid learning.